Tax risk in automotive manufacturing companies in Indonesia: The effect of tax avoidance with CSR as a moderator - Anjarwati, Emilia Eni; Irawan, Ferry (WIM Solusi Prima, 2025)
This quantitative study aims to determine whether tax avoidance is able to influence the increase in tax risk in the future and whether Corporate Social Responsibility (CSR) is able to moderate the relationship between the two variables. The population in this study is Automotive Manufacturing Companies in Indonesia. By using purposive sampling technique, a sample of 50 observations was obtained with a research period of 2020-2024. By using the STATA 13 testing tool, the results of the study showed that tax avoidance did not have a significant effect on future tax risk and CSR was able to moderate the relationship between the two variables.